The In Vitro Antifungal Impact of Secondary Metabolites from Trichoderma sp. on Fusarium sp. - Uswatun Hasanah; Arika Purnawati; Herry Nirwanto (Kadiri University - Faculty of Agriculture, 2023)
Fusarium sp. is a significant pathogenic fungus responsible for causing wilt in various plants, including chilies, eggplants, and shallots. One approach to address this issue involves utilizing secondary metabolites from the fungus Trichoderma sp. These metabolites were applied at concentrations of 10%, 20%, and 30% alongside a fungicide called M-Dithane 45, following the recommended dosage specified on the packaging. This research aims to evaluate the impact of these secondary metabolites in suppressing the Fusarium sp. pathogen. The study occurred at the Plant Health Laboratory I within the Faculty of Agriculture at Universitas Pembangunan Nasional “Veteran” East Java from October to December 2022. It adopted a single-factor, Completely Randomized Design (CRD), and data analysis was carried out using R-studio software. In vitro analysis was conducted through the dual culture technique on a PDA medium, assessing inhibition percentages and observing the morphology of Fusarium sp. fungi. The results demonstrated that the highest inhibition percentage of Fusarium sp. occurred at a 30% concentration, reaching 26% compared to the control group. Morphological examinations of Fusarium sp. indicated that all treatments affected the growth of abnormal hyphae, including bending, curling, coiling, and lysis.